Myocardial infarction is sufficient to increase GLP‐1 secretion, leading to improved left ventricular contractility and mitochondrial respiratory capacity. Issue 12 (16th August 2018) - Diebold, Sebastian; Moellmann, Julia; Kahles, Florian; Haj‐Yehia, Elias; Liehn, Elisa A.; Nickel, Alexander; Lebherz, Corinna; Maack, Christoph; Marx, Nikolaus; Lehrke, Michael
Abstract : Myocardial infarction causes rapid impairment of left ventricular function and requires a hypercontractile response of non‐infarcted tissue areas to maintain haemodynamic stability. This compensatory adaptation is mediated by humoral, inflammatory and neuronal signals. GLP‐1 is an incretin hormone with glucoregulatory and cardioprotective capacities and is secreted in response to nutritional and inflammatory stimuli. Inactivation of GLP‐1 is caused by the ubiquitously present enzyme DPP‐4. In this study, circulating concentrations of GLP‐1 were assessed after myocardial infarction and were evaluated in the light of metabolism, left ventricular contractility and mitochondrial function. Circulating GLP‐1 concentrations were markedly increased in patients with acute myocardial infarction. Experimental myocardial infarction by permanent LAD ligation proved sufficient to increase GLP‐1 secretion in mice. This took place in a time‐dependent manner, which coincided with the capacity of DPP‐4 inhibition, by linagliptin, to augment left ventricular contractility in a GLP‐1 receptor‐dependent manner. Mechanistically, DPP‐4 inhibition increased AMPK activity and stimulated the mitochondrial respiratory capacity of non‐infarcted tissue areas. We describe a new functional relevance of inflammatory GLP‐1 secretion for left ventricular contractility during myocardial infarction.